What women want before justice: examining justice initiatives to challenge violence against women in the DRC - Sahin, Bilge (International journal of transitional justice)
While the realization of women’s rights has increased significantly in the Democratic Republic of the Congo, Congolese women’s struggle is often obscured by certain international actors actively pushing for social change in the region. Those who are politically active in the area tend to forget that it is not the mere act of imposing policies that effects change, but rather actively involving Congolese women in decision-making processes. This article examines the way conflict-related sexual violence crimes are interpreted by donors, international organizations and international nongovernmental organizations, and what is implemented to challenge these acts of violence in accordance with the needs and expectations of Congolese women. By looking at current feminist discourse on conflict, security and development, the article aims to highlight the failures in implementing justice initiatives without input from women on the ground.